2016
DOI: 10.1177/0898264316668936
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Group-Based Behavioral Intervention on Dietary Behaviors in Older Adults

Abstract: A 12-week, behavioral nutrition intervention improved dietary behaviors. Behavioral interventions may be a low-cost way to improve dietary behaviors among older adults, potentially affecting population health significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Indeed, both healthy food and physical exercise modulate the cellular and molecular processes in the brain that are vital for cognitive health, including the optimization of growth factors such as brainderived neurotrophic factor (e.g., Chie et al, 2017). Intervention studies have shown that physical activity and optimized dietary behaviors increase cognitive functioning in older age and that greater physical activity is bene cial in protecting against cognitive decline (Schlaff et al, 2018).…”
Section: Crucial Lifestyle Factors Which Prevent Cognitive Declinementioning
confidence: 99%
“…Indeed, both healthy food and physical exercise modulate the cellular and molecular processes in the brain that are vital for cognitive health, including the optimization of growth factors such as brainderived neurotrophic factor (e.g., Chie et al, 2017). Intervention studies have shown that physical activity and optimized dietary behaviors increase cognitive functioning in older age and that greater physical activity is bene cial in protecting against cognitive decline (Schlaff et al, 2018).…”
Section: Crucial Lifestyle Factors Which Prevent Cognitive Declinementioning
confidence: 99%
“…Different studies on interventions designed to increase social activity (e.g., communication training) showed a positive influence on cognitive factors ( Videler et al, 2020 ; e.g., Bambini et al, 2020 ; Christelis and Dobrescu, 2020 , for a meta-analysis). Second, physical health-related activities, such as physical exercise or healthy food interventions, were shown to prevent cognitive decline (e.g., Mediterranean diet or physical activity goals; Abbott et al, 2004 ; Lautenschlager et al, 2008 ; Coelho et al, 2009 ; Audiffren et al, 2011 ; Morris et al, 2015 ; Schlaff et al, 2018 ). Also, positive effects of coordination training interventions or so-called “brain gym exercises” were reported for working memory performance and well-being in older male adults ( Voelcker-Rehage et al, 2011 ; Tootak and Abedanzadeh, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, intervention studies have shown that physical activity and optimized dietary behaviors increase cognitive functioning in older age. Increased physical activity is beneficial in protecting against cognitive decline [ 56 ].…”
Section: Introductionmentioning
confidence: 99%